Fast-deactivating calcium channels in chick sensory neurons (The Rockefeller University Press, 1988)
Whole-cell Ca and Ba currents were studied in chick dorsal root ganglion (DRG) cells kept 6-10 in culture. Voltage steps with a 15- microseconds rise time were imposed on the membrane using an improved patch-clamp circuit. Changes in membrane current could be measured 30 microseconds after the initiation of the test pulse. Currents through Ca channels were recorded under conditions that eliminate Na and K currents. Tail currents, associated with Ca channel closing, decayed in two distinct phases that were very well fitted by the sum of two exponentials. The time constants tau f and tau s were near 160 microseconds and 1.5 ms at -80 mV, 20 degrees C. The tail current components, called FD and SD (fast-deactivating and slowly deactivating), are Ca channel currents. They were greatly reduced when Mg2+ replaced all other divalent cations in the bath. The SD component inactivated almost completely as the test pulse duration was increased to 100 ms. It was suppressed when the cell was held at membrane potentials positive to -50 mV and was blocked by 100-200 microM Ni2+. This behavior indicates that the SD component was due to the closing of the low-voltage-activated (LVA) Ca channels previously described in this preparation. The FD component was fully activated with 10-ms test pulses to +20 mV at 20 degrees C, and inactivated to approximately 30% during 500-ms test pulses. It was reduced in amplitude by holding at - 40 mV, but was only slightly reduced by micromolar concentrations of Ni2+. Replacement of Ca2+ with Ba2+ increased the FD tail current amplitudes by a factor of approximately 1.5. The deactivation kinetics did not change (a) as channels inactivated during progressively longer pulses or (b) when the degree of activation was varied. Further, tau f was affected neither by changing the holding potential nor by varying the test pulse amplitude. Lowering the temperature from 20 to 10 degrees C decreased tau f by a factor of 2.5. In all cases, the FD component was very well fitted by a single exponential. There was no indication of an additional tail component of significant size. Our findings indicate that the FD component is due to closing of a single class of Ca channels that coexist with the LVA Ca channel type in chick DRG neurons.